2018
DOI: 10.1002/jcp.27030
|View full text |Cite
|
Sign up to set email alerts
|

Infection‐associated epigenetic alterations in gastric cancer: New insight in cancer therapy

Abstract: Gastric cancer risk is higher for malignancies motivated by bacterial and viral infections. Epigenetic abnormalities including DNA methylation, histone modifications, and noncoding RNAs are important regulatory key players in gastric cancer development in infected patients. Epigenetic memory restoration is an extremely interesting phenomenon which should be considered in therapeutic approaches. In vitro and in vivo antiviral treatments in combination with epigenetic therapeutic strategies along with standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…However, the molecular mechanisms of DNA methylation induced by EBV infection is still largely unknown (Choi et al, ). In addition, there is evidence that the human CMV is associated with many human malignancies, but its role in GC is controversial (Fattahi et al, ; Fattahi et al, ). To the best of our knowledge, no previous study has revealed the association of CYLD expression and promoter methylation with infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms of DNA methylation induced by EBV infection is still largely unknown (Choi et al, ). In addition, there is evidence that the human CMV is associated with many human malignancies, but its role in GC is controversial (Fattahi et al, ; Fattahi et al, ). To the best of our knowledge, no previous study has revealed the association of CYLD expression and promoter methylation with infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…DNMT3A and DNMT3B are able to act as de novo DNA methyl transferases, whereas DNMT2 has been identified as a tRNA methyltransferase [ 76 , 77 , 78 , 79 ]. DNMTs play a pivotal role in gene transcription regulation during normal development, and although expression itself does not necessarily mean increased functionality, aberrant DNMT expression has been related to carcinogenesis in almost all malignancies, including GC, as inactivation of several tumor suppressor genes occurs in a DNMT-dependent manner [ 80 , 81 ]. In a study by Yang et al, DNMTs were found highly expressed in GC tissue specimens (54 patients).…”
Section: Epigenetics Of Gcmentioning
confidence: 99%
“…Multiple pathways in gastric carcinogenesis regulate DNMT expression. H. pylori and EBV infections result in chronic inflammation within the gastric mucosa, affecting epigenetic machinery and modulating DNMT expression through the release of oncogenic proteins such as CagA,,and inflammatory responses mediated by tumor-associated macrophages (TAMs) [ 12 , 81 ]. Moreover, DNMT1 expression is regulated by the tumor suppressor APC through the downstream pathway APC/β-catenin/TCF [ 93 ], and mutation or loss of APC may result in uncontrolled DNMT1 expression.…”
Section: Epigenetics Of Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also reported that exposure of gastric cancer cells to nitric oxide (NO) produced induced DNA methylation by enhancing DNMT enzymatic activity [102][103]. Furthermore, infectious agents can induce epigenetic modifications, and be the most common complications in gastric cancer [104][105]. Infections hijack the host DNA methylation mechanism via increasing DNMTs in order to control host transcription to their benefit.…”
Section: Expression Of Dnmts and Susceptibility To Infections In Gastmentioning
confidence: 99%